Fire retarded polyurethane foam composites based on steel slag/ammonium polyphosphate system: A novel strategy for utilization of metallurgical solid waste. (25th October 2021) - Yang, Sujie; Liu, Xiuyu; Tang, Gang; Long, Hongming; Wang, Bibo; Zhang, Hao; Ji, Yilong; Yang, Yadong
Abstract: A series of FR‐RPUF composites were prepared by a one‐step water foaming process with ammonium polyphosphate (APP) and steel slag (SS) as flame retardants. Thermogravimetric analysis (TG), limiting oxygen index (LOI), UL‐94 vertical combustion test, microscale combustion calorimetry (MCC), TG‐Fourier transform infrared spectrometry (TG‐FTIR), scanning electron microscopy (SEM), Raman spectra and FTIR were used to investigate the thermal stability, flame retardancy, combustion performance, gas phase products, and char residue morphology of FR‐RPUF composites. TG test results showed that the initial decomposition temperature (T‐5wt% ) and char residue rate at 700°C of RPUF/APP/SS composites were significantly enhanced by the addition of APP and SS, and the thermal stability of the composites was improved. Flame retardant test results confirmed the significantly increased LOI values of RPUF/APP/SS composites with V‐0 rating. TG‐FTIR also confirmed the obviously decreased release of toxic gases and flammable gases in the combustion of RPUF/APP/SS composites. SEM and Raman spectra of char residues for the composites suggested that APP/SS system improved the compactness and graphitization degree of char layer for RPUF/APP/SS composite. The above researches provide a new strategy for the utilization of SS in fire safety engineering.